1977
DOI: 10.1007/bf01670281
|View full text |Cite
|
Sign up to set email alerts
|

Influence de la photopériode sur l'ultrastructure de l'épiphyse avant et pendant la phase génitale saisonniére chez la femelle du lérot (Eliomys quercinus)

Abstract: The pinealocyte of the female garden dormouse presents ultrastructural characteristics correlated with the sexual cycle. In winter, during the period of sexual quiescence, the pinealocyte is very rich in liposomes, myelinic bodies and lysosomes; the same holds during the summer quiescence state. These organelles and a great number of intracellular vacuoles are very well developed in dormice artificially maintained in anoestrous during the normal sexual activity period by light deprivation. In spring liposomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0
2

Year Published

1979
1979
1996
1996

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 9 publications
1
5
0
2
Order By: Relevance
“…The two characteristic ultrastructural aspects of the pinealocytes previously described, i.e., the anoestrus-related aspect seen in hibernating animals (Richoux et aI., 1975) or in darkened animals during spring or summer (Roux et al, 1977) and the sexual activityrelated aspect observed in normal sexually active animals in spring (Roux et al, 1977) or in continuously illuminated animals during the winter , could again he demonstrated in the present material.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The two characteristic ultrastructural aspects of the pinealocytes previously described, i.e., the anoestrus-related aspect seen in hibernating animals (Richoux et aI., 1975) or in darkened animals during spring or summer (Roux et al, 1977) and the sexual activityrelated aspect observed in normal sexually active animals in spring (Roux et al, 1977) or in continuously illuminated animals during the winter , could again he demonstrated in the present material.…”
Section: Discussionsupporting
confidence: 61%
“…We demonstrated the typical ultrastructural aspects of this pineal endocrine cell, varying with the photoperiodicity and sexual activity (Roux et al, 1977(Roux et al, , 1979(Roux et al, , 1981.…”
Section: Introductionmentioning
confidence: 98%
“…The presence of 5-HT in DCV varies in different species, depending upon the quantity of remaining 5-HT (which is not rapidly metabolized) and probably also, in a given species, upon daily changes ; the circadian rhythm of 5-HT and its related indoleamines is well known (Quay, 1974 ;Wurtman et al, 1968 ;Axelrod, 1974Axelrod and Zatz, 1977 (Roux et al, 1977) and after blinding and continuous darkness in hamsters (Sheridan, 1975) (Romijn, 1975), hamsters (Lin et al, 1975 ;Sheridan, 1975) and mice (Pellegrino de Iraidi, 1969) ; administration of parasympatholytic drugs in rabbits (Romijn, 1976) ; surgical castration in rats (Karasek et a/., 1976) ; injection of human chorionic gonadotropin (HCG) and pregnant mare serum gonadotropin (PMSG) in rats (Karasek and Marek, 1978) ; in the presence of norepinephrine (NE) or dibutyryl-cyclic-adenosine 3'-5'-monophosphate (db-c-AMP) in rat pineals cultured in vitro (Karasek, 1974) or in rabbits (Romijn and Gelsema, 1976). It has also been shown that a mean number of DCV in rabbits (Quay, 1974 ;Ebels, 1976 ;Benson et al, 1976 Finally, taking into account the detailed discussions of previous papers on reptiles, birds and mammals (Collin and Meiniel, 1971 ;Collin, , 1979Collin et al, 1977a, b ;Juillard and Collin, 1978) …”
Section: Pinealocyte Secretory Processesmentioning
confidence: 99%
“…All the animals stayed in permanent anoestrus even at long-term. The Kappers, 1969Kappers, , 1976Reiter, 1978 (Roux et Richoux et al, 1975 ;Roux et al, 1977Roux et al, , 1979 (Zweens, 1963), du taux d'hormone gonadotrope circulante (Zweens, 1965 ;Karasek et Marek, 1978) nous font penser, avec Pevet (1979) (Roux et al, 1977). Rappelons que tous ces animaux sont en état d'anaestrus.…”
unclassified
“…Des vacuoles intracellulaires semblables ont été observées dans l'épiphyse de divers Mammifères (revue de Pevet, 1979). Pevet et Smith (1975) (Pevet, 1979 (Roux et al, 1977 ;Cordonnier et Roux, 1978). Ces organites sont rares chez les Lérots en état d'anoestrus : animaux hibernants, privés de lumière ou énucléés.…”
unclassified